2021
DOI: 10.1155/2021/6661534
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid Enhanced the Antitumor Effect of Cisplatin on Orthotopic Osteosarcoma by ROS‐PI3K/AKT Signaling and Attenuated Osteolysis

Abstract: Osteoclasts can interact with osteosarcoma to promote the growth of osteosarcoma. Cisplatin is common in adjuvant chemotherapy of osteosarcoma. However, due to chemoresistance, the efficacy is profoundly limited. Previous studies have found that zoledronic acid (ZA) has osteoclast activation inhibition and antitumor effect. However, the combined effect of ZA and cisplatin on osteosarcoma remains unclear. In vitro, the effects of ZA and cisplatin alone or in combination on 143B cell activity, proliferation, apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
(66 reference statements)
0
26
0
Order By: Relevance
“…Right now, almost all the mechanisms of ferroptosis are associated with reactive oxygen species (ROS) ( Li et al, 2020 ). Given the role of ZA in regulating ROS production ( Sehitoglu et al, 2015 ; Wang et al, 2018 ; Liu et al, 2021 ), here we investigated whether ZA suppresses the growth of osteoclast by accelerating ferroptosis. We found that the ferroptosis-related marker such as the levels of Fe 2+ , MDA content, ROS level was obviously increased in the osteoclasts treated with ZA, suggesting the ZA induced the ferroptosis of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Right now, almost all the mechanisms of ferroptosis are associated with reactive oxygen species (ROS) ( Li et al, 2020 ). Given the role of ZA in regulating ROS production ( Sehitoglu et al, 2015 ; Wang et al, 2018 ; Liu et al, 2021 ), here we investigated whether ZA suppresses the growth of osteoclast by accelerating ferroptosis. We found that the ferroptosis-related marker such as the levels of Fe 2+ , MDA content, ROS level was obviously increased in the osteoclasts treated with ZA, suggesting the ZA induced the ferroptosis of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Among BPs, Zoledronate (ZOL), Pamidronate (PAM) and Neridronate (NRD) are the most-used anti-osteoporotic agents in children. ZOL is used in children affected by cancer who are disease free for a prolonged time and also in cases of bone metastases [ 149 ], as adjuvant chemotherapy to reduce skeletal events [ 150 ]. Recently, Liu et al observed in their study a reduction in osteolysis with combined use of Cisplatin and ZOL (CisZol) in OS patients, due to a strong inhibition of osteoclastic differentiation [ 150 ].…”
Section: Therapy and Preventionmentioning
confidence: 99%
“…Excessive amounts of FPP and GGPP lead to protein prenylation impairment, this is a potential pathological feature of osteoporosis (Zameer et al, 2018). ZA is known as the gold standard for the treatment of osteoporosis because of its recognized role in attenuating bone resorption and osteoclast apoptosis by inhibiting FPPS in the mevalonate pathway (Figure 2) (Tang et al, 2017;Zameer et al, 2018;Chandra and Rajawat, 2021;Chen et al, 2021;Munoz et al, 2021). Targeted inhibition of FPPS by ZA blocks the synthesis of FPP and the downstream product GGPP, which prevents the prenylation of Rab GTPases (e.g., members of the Ras superfamily) and their binding proteins (Kimachi et al, 2011;Zameer et al, 2018;Soysa and Alles, 2019).…”
Section: Zoledronic Acid Induces Apoptosis In Osteoclastsmentioning
confidence: 99%